2022
DOI: 10.3390/ma16010140
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies of the Dielectric Properties of Polyester Imide Composite Membranes Containing Hydrophilic and Hydrophobic Mesoporous Silica Particles

Abstract: In this paper, comparative studies of hydrophilic and hydrophobic mesoporous silica particles (MSPs) on the dielectric properties of their derivative polyester imide (PEI) composite membranes were investigated. A series of hydrophilic and hydrophobic MSPs were synthesized with the base-catalyzed sol-gel process of TEOS, MTMS, and APTES at a distinctive feeding ratio with a non-surfactant template of D-(-)-Fructose as the pore-forming agent. Subsequently, the MSPs were blended with the diamine of APAB, followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Likewise, the pore volume for ARS is 0.04 cm 3 /g, and for AMS, it escalates to 0.42 cm 3 /g, marking an approximately tenfold increase. This confirms the successful preparation of mesoporous materials from aminosilane-functionalized silica spheres [34].…”
Section: Bet Analysis Of Mesoporous Propertiessupporting
confidence: 72%
See 1 more Smart Citation
“…Likewise, the pore volume for ARS is 0.04 cm 3 /g, and for AMS, it escalates to 0.42 cm 3 /g, marking an approximately tenfold increase. This confirms the successful preparation of mesoporous materials from aminosilane-functionalized silica spheres [34].…”
Section: Bet Analysis Of Mesoporous Propertiessupporting
confidence: 72%
“…After modification by APTES, signals for T 2 and T 3 from the organic silicon series were observed at chemical shifts of −63 ppm and −66 ppm, respectively. By consolidating the evidence from 13 C SS-NMR and 29 Si SS-NMR, it can be affirmed that the -NH 2 active functional group has been successfully bonded within the SiO 2 mesoporous material [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Yeh et al [30] studied the impact of hydrophilic and hydrophobic mesoporous silica particles (MSPs) on the dielectric properties of composite membranes derived from polyester imide (PEI). The study revealed a clear trend in the dielectric constant of the membranes: PEI containing hydrophilic MSPs > PEI > PEI containing hydrophobic MSPs.…”
Section: Contributionsmentioning
confidence: 99%
“…Figure 3 shows the representative spectra of the 13 Moreover, Figure 4 showed the representative spectra of the 29 Si-NMR spectra of asprepared flexible silica aerogels (i.e., FSA, FSA-M1, FSA-M5, FSA-M10, and FSA-T10). For example, the characteristic signal values of -Si(OSi)3 (denoted by T3) and -Si(OSi)2OH (denoted by T 2 ) can be assigned at the positions of −67.1 ppm and −57.5 ppm, respectively [28]. Moreover, Figure 4 showed the representative spectra of the 29 Si-NMR spectra of asprepared flexible silica aerogels (i.e., FSA, FSA-M1, FSA-M5, FSA-M10, and FSA-T10).…”
Section: Spectroscopic Studies (Ftir and Nmr) Of Eddet Vtms Precursormentioning
confidence: 99%
“…Moreover, Figure 4 showed the representative spectra of the 29 Si-NMR spectra of asprepared flexible silica aerogels (i.e., FSA, FSA-M1, FSA-M5, FSA-M10, and FSA-T10). For example, the characteristic signal values of -Si(OSi) 3 (denoted by T3) and -Si(OSi) 2 OH (denoted by T 2 ) can be assigned at the positions of −67.1 ppm and −57.5 ppm, respectively [28].…”
Section: Spectroscopic Studies (Ftir and Nmr) Of Eddet Vtms Precursormentioning
confidence: 99%